Cytotoxic Activity of Castanopsis argentea (Blume) A.DC. Extract and Fraction on MCF-7 Breast Cancer Cell - Nuringtyas, Tri Rini; Nastiti, Anisa Diana; Surta, Muhammad Imam; Lailaty, Intani Quarta; Damayanti, Frisca (Fakultas Biologi Universitas Gadjah Mada, 2025)
Marine algae is a biological source that is rich in bioactive activity. Marine algae is an important source of macronutrients, especially proteins and lipids, as well as micronutrients such as vitamins and minerals along with dietary fiber and other minoritarian constituents such as polyphenols. This study aimed to determine the antioxidant of hydrolysate protein of Sargassum sp. as. The work method was started by collecting Sargassum sp. in the intertidal zone of the South Coast of Gunungkidul, Yogyakarta and then brought to the laboratory for extraction. Protein hydrolysate was obtained by protein extraction using phosphate buffer and triRNA kit. Several buffers was used to optimize the extraction, namely PBS buffer, Tris HCl buffer and plant extraction buffer The protein obtained were evaluated in the SDS-PAGE electrophoresis. The isolated protein subjected for the trypsin digestion to obtain the hydrolysate protein then followed by antioxidant assays using DPPH test. Data analysis was carried out using ANOVA statistics for the antioxidant test. Several ratios of trypsin and protein are used to find the optimal ratio to produce protein hydrolysate. From the result it was observed that the best buffer solvent to use was Tris HCl buffer for the isolation of Sargassum sp. This can affect the protein profile of the Sargassum sp protein hydrolysate. by producing higher protein precipitates than other buffer types.